2021
DOI: 10.21203/rs.3.rs-704894/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of the Prognosis Related Genes in HER2+ Breast Cancer Based on Weighted Gene Co-expression Network Analysis

Abstract: Background: Breast cancer is one of the malignant tumors that threaten women's health, with HER2+ breast cancer being more aggressive. In this study, bioinformatics methods were used to find potential key genes in HER2 + for diagnosis and treatment.Methods: Datasets of HER2+ breast cancer and normal tissue samples retrieved from TCGA databases were subjected to DEGs analysis using R software. Then WGCNA is constructed for DEGs. The key gene co-expression modules were then subjected to GO and KEGG pathway enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…More recently, bioinformatics has been widely applied to oncological and non-oncological diseases, including sepsis (Lai et al, 2020;Li Z. et al, 2021;Wu Z. et al, 2021). Previous studies have focused on differential genes in the blood of Sepsis patients and revealed the molecular pathways of differential genes (Chen et al, 2021). However, the common diagnostic genes of Sepsis and MetS and the shared metabolic pathways remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, bioinformatics has been widely applied to oncological and non-oncological diseases, including sepsis (Lai et al, 2020;Li Z. et al, 2021;Wu Z. et al, 2021). Previous studies have focused on differential genes in the blood of Sepsis patients and revealed the molecular pathways of differential genes (Chen et al, 2021). However, the common diagnostic genes of Sepsis and MetS and the shared metabolic pathways remain unclear.…”
Section: Introductionmentioning
confidence: 99%